An investigation into current protocols and radiographer opinions on contrast extravasation in Irish CT departments. Issue 4 (November 2017) - Cleary, N.; McNulty, J.P.; Foley, S.J.; Kelly, E.
Abstract: Background: Iodinated contrast extravasation is a serious complication associated with intravenous administration in radiology. Departmental protocols and the radiographer's approach on both prevention techniques and treatment will affect the prevalence of extravasation, and the eventual outcome for the patient when it does occur. Aims: To examine contrast extravasation protocols in place in Irish CT departments for alignment with European Society of Urogenital Radiology (ESUR) Guidelines (2014); to establish radiographer's opinions on contrast extravasation; and to examine radiographer adherence to protocols. Methods: Contrast extravasation protocols from a purposively selected sample of CT departments across Ireland (n = 6) were compared to ESUR guidelines, followed by an online survey of CT radiographers practicing in the participating centres. Results: All participating CT departments (n = 5) had written protocols in place. High risk patients, such as elderly or unconscious, were identified in most protocols, however, children were mentioned in just one protocol and obese patients were not specified in any. The response rate of CT radiographers was 23% (n = 24). 58% (n = 14) of respondents indicated that contrast extravasation was more likely during CTA examinations. While high levels of confidence in managing extravasation were reported, suggested treatment approaches, and confidence in same, was more variable. Clinical workload in CT departments was also identified as a factor impacting on patient care and management. Conclusion: While contrast extravasation protocols were generally in line with ESUR Guidelines, high risk patients may not be getting sufficient attention. More radiographer awareness of patient monitoring needs, particularly in busy departments with a heavy workload may also reduce extravasation risk, and improve management of same. Highlights: Irish protocols on contrast extravasation are generally in line with international guidelines. Irish protocols may benefit from more regular review. Certain patient groups could be given more consideration in practise. Education and training for radiographers on extravasation, particularly on treatment methods, is recommended. In busy modern CT departments, Irish radiographers may not always communicate optimally with patients.